Association of serum paraoxonase concentration with serum lipid levels and bone mineral density measurements in early postmenopausal women - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (TAYLOR & FRANCIS LTD, 2015)
Objective To determine the association of serum paraoxonase concentration with serum lipid levels and bone mineral density in early postmenopausal Turkish women. Design One hundred healthy postmenopausal women were included in a cross-sectional study in a University hospital clinic. Blood was drawn from women who had bone mineral density (BMD) measurements during routine visits. BMD of the lumbar vertebrae was measured by dual-energy X-ray absorptiometry. The serum paraoxonase concentration and serum lipid levels were measured. Women were divided into two groups: those with normal lumbar vertebrae BMD and those with osteopenic lumbar vertebrae. Serum paraoxonase concentration was compared between the groups. The correlation between serum paraoxonase concentration and bone mass parameters was performed using Pearson's test. Results The paraoxonase concentration in the osteopenic group was significantly lower than in the group with normal lumbar vertebrae BMD. The paraoxonase concentration was moderately correlated with total cholesterol, low density lipoprotein cholesterol and triglyceride levels among early postmenopausal Turkish women. Conclusions Early postmenopausal women with osteopenic lumbar vertebrae have significantly lower paraoxonase concentration than those with normal lumbar vertebrae BMD. Further studies are needed to clarify the associations between the osteoporosis risk factors and paraoxonase concentration during late postmenopausal years.
Keywords: POSTMENOPAUSE; PARAOXONASE; BONE MINERAL DENSITY; OSTEOPENIA; VITAMIN-C; CHOLESTEROL; DIET; MASS; DIFFERENTIATION; CALCIFICATION; REPLACEMENT; PARADOX; RICH; FAT